Factors Associated with the Level of Depression among Elderly Women Residing in Old Age home of Devghat, Tanahu - Gauli, Sirisa; Shrestha, Gauri (Nepalese Journal of Statistics, 2017)
Background: There has been considerable increase in elderly population all over the world and this population is thought to be at a greater risk of depression which is a major health problem. Comparatively, depression is found to be at a higher rate among women compared to men. Objective: This study aims to identify the factors influencing the level of depression among elderly women residing in old age home of Devghat, Tanahu. Materials and Methods: This study is entirely based on primary data taking a total population (116) of elderly women from face to face interview using the short version of Geriatric Depression Scale (GDS), Instrumental Activities of Daily Living Scale (IADL) and socio-demographic interview schedule. To gather information, mobile data collection tool i.e. GIS Cloud was used. Data was analyzed using descriptive and inferential statistical methods. To determine the significant factors influencing depression among the respondents, multinomial logistic regression model was used. Results: The mean score obtained from GDS was 7.52 ranging from 2 to 14. About 24% of the respondents had mild depression and 47% of them had severe depression. More than 66% of them were from rural area. About 50% of respondents had no financial support; about 53% of them were found with feeling of loneliness. Regression analysis showed that the factors like age at marriage, type of place of previous residence, financial support, satisfaction of living condition, feeling of loneliness, and IADL score were found to be significantly associated with level of depression. Conclusion: The result of the study indicates that most of the elderly women living in the old age home were suffering from depression. Some actions like raising fund through charity approach, counseling, promoting social volunteers or family members to visit old age home and supporting them, etc. should be addressed from the concerned authorities so that depression can be reduced which will support to the well-being and superior life of elderly women. Nepalese Journal of Statistics, 2017, Vol. 1, 29-40